Morphology and molecular data of the species of Suillus (Suillaceae, Boletales) associated with Pinus sibirica at the European northeast of Russia - Palamarchuk, Marina A.; Kirillov, Dmitry V.; Shadrin, Dmitry M. (Phytotaxa, 2021)
The genus Suillus represents the largest genus of the family Suillaceae, forming ectomycorrhizae with coniferous trees. Here, we presented the first results of molecular research (nrITS1-5.8S-ITS2 rDNA sequences) of the specimens of Suillus, forming ectomycorrhizae with Pinus sibirica, at the territory of European northeast of Russia. The six taxa (Suillus acidus var. intermedius, S. placidus, S. plorans subsp. plorans, S. plorans subsp. cyanescens, S. punctipes and S. sibiricus) are identified based on morphological and molecular evidence. The key for identification, full morphological descriptions, the color photos of basidiomata and information on their ecology and distribution in Russia and world are presented for these taxa. On the basis of the molecular approach, we confirmed the relevance of subspecies Suillus plorans subsp. cyanescens previously described only by morphological features. BLAST-analysis of Suillus placidus with untypical for this species brown pileus revealed 99% identity with the specimens of S. placidus from Asia, for which the color of pileus varies from white to brown.